Physical, psychological and demographic factors associated with military discharge: a systematic review - Gabriel Luis Moreira Fidelis; Maria Elisa Koppke Miranda; Priscila dos Santos Bunn (Motriz: Revista de Educacao Fisica, 2021)
Abstract Aims: The present study is a review focused on analyzing the physical, psychological, and demographic factors that lead recruits to be dismissed or to request their dismissal during basic military training periods. Methods: This study is a systematic review of cohort studies. The following databases were searched in June 2019 and updated in July 2020: Embase, LILACS, CINAHL, Cochrane, MEDLINE, SCOPUS, SPORTDiscus, Web of Science, and Science Direct databases. The MeSH descriptors military personnel, risk factors, and discharge were used to elaborate the search equations. Reference lists were explored to find studies that examined the association between physical, psychological, and demographic factors that lead recruits to be discharged. The following data were extracted from the studies: profile of the participants, sample size, type of risk factors, the duration of follow-up, and the results of the statistical analysis carried out in the studies included. The risk of bias was analyzed with the Newcastle-Ottawa Scale for cohort studies. Results: A total of 531 titles were retrieved from the databases, and eight articles met the eligibility criteria. The results showed the factors associated with discharge, in descending order: musculoskeletal injuries and other medical questions, depressive and behavioural disorders, performance in physical fitness tests, and others. Factors such as educational level, alcohol use, history of suicide attempt, and imprisonments were not associated with an increased risk of being discharged. Conclusion: Musculoskeletal injuries, depression, running performance, previous physical exercise practice, and demographic factors were associated with an increased risk of being discharged.